Effectiveness of policy instrument mixes for forest conservation in the tropics – Stakeholder perceptions from Ecuador, the Philippines and Zambia. (April 2023) - Fischer, Richard; Lippe, Melvin; Dolom, Priscilla; Kalaba, Felix Kanungwe; Tamayo, Fabian; Torres, Bolier
Abstract: Effective policy instruments are needed to halt or even reverse ongoing tropical deforestation. In this context, the increased focus on incentive-based instruments on the one hand and the unchanged support for classical command and control measures on the other, call for smart policy mixes. We aim to identify the effectiveness of policy instruments and of policy mixes based on stakeholder perceptions. We also aim to analyze stakeholders' power in order to appraise the relevance of different instruments on national forest policy agendas. Our study implements related research based on more than 100 key informant interviews along the pantropical country-context of Ecuador, Philippines and Zambia. Principal component analysis is applied to identify forest policy mixes, and social network analysis to quantify stakeholder power. Our results show that despite recent discussions and support for incentive-based mechanisms like REDD+ and market-based solutions, regulative instruments are equally advocated. There is an astonishing congruence in the support of national stakeholders for specific policy instruments like reforestation subsidies, protected areas, and measures to combat illegal logging. But despite this high congruence, the policy instruments need to be implemented in country-specific combinations, because we find diverging stakeholder perceptions on national policy mixes. These diverging perceptions require good governance within the related decision and implementation processes. Whereas NGOs in general have a stronger focus on regulatory instruments, enterprises show more support for economic measures. International organizations have the most balanced perception in this respect, followed by national governments. National governments are the most powerful stakeholders. Their power is required to coordinate decision processes and ensure implementation. The almost equally powerful role of international organizations poses questions of ownership. We present a detailed analysis of policy mixes and recommendations for each of the three countries. Highlights: Regulative policy instruments remain important despite the current focus on economic incentives. Protected areas and reforestation measures scored as most effective policy instruments. Implementation in country-specific policy mixes is decisive. National governments and international organizations were most powerful stakeholders.